An Enormous Interstitial Mestizo? The (Im)possibility of Eurasian Identity in Dutch Postcolonial Novels - Boudewijn, Petra R. (Werkwinkel, 2016)
This article examines the (im)possibility of Eurasian identity in Dutch postcolonial novels by second-generation authors such as Marion Bloem and Adriaan van Dis. As a result of Indonesia’s decolonisation 300.000 Dutch nationals came from the former Dutch East Indies to the Netherlands. Among them was a large group of Eurasians, people of mixed Dutch and Indonesian descent. Many of whom had never set foot on the so-called motherland. Although Eurasians had belonged to the European community in the tropics, they were perceived as immigrants by the Dutch government and were subjected to an aggressive, far-reaching assimilation policy - fearing they would otherwise become a major social problem. Their offspring, the so-called second generation, is often assumed to struggle with their identity while growing up in a postcolonial society that did not tolerate cultural differences at the time. What constitutes a Eurasian identity, and can such identities exist after the enforced assimilation of Eurasians in the Netherlands? How do second-generation authors look upon their Eurasian background and how do they portray these assumed identity struggles in postcolonial literature? The texts in question are discussed in relation to theories of hybridity. It is argued that the widespread notion that Eurasians either fall between two stools or grow into examples of hybrid identity are not foregone conclusions.